Phosphorus-doped helical carbon nanofibers as enhanced sensing platform for electrochemical detection of carbendazim. (15th April 2017) - Cui, Rongjing; Xu, Dong; Xie, Xiaohan; Yi, Yuyang; Quan, Ying; Zhou, Maixi; Gong, Jinjian; Han, Zhida; Zhang, Genhua
Highlights: Phosphorus-doped helical carbon nanofibers (P-HCNFs) with high P content were synthesized. P-HCNFs have helical structure and rapid apparent heterogeneous electron transfer. P-HCNFs were firstly used to develop an amperometric sensor for carbendazim detection. Presented sensor has high sensitivity, wide linear range, and low detection limit. Abstract: A combined chemical vapor deposition with high-pressure annealing has been developed for the production of phosphorus-doped helical carbon nanofibers (P-HCNFs). The resulting P-HCNFs have a large specific surface area, well-defined three-dimensional hierarchical helical structure and rapid apparent heterogeneous electron transfer. Based on the high electrocatalytic activity, the P-HCNFs were used to develop an amperometric sensor for carbendazim detection. The experimental results demonstrated that the sensor is promising for the determination of carbendazim in food samples due to the high sensitivity, wide linear range and low detection limit.